Antiviral death punch by ADP-ribosylating bacterial toxins. Issue 10 (October 2022) - Shaidullina, Aisylu; Harms, Alexander
Abstract : Toxin–antitoxin systems can defend bacteria against phages by shutting down infected cells, but the links between their molecular mechanisms and biological functions have remained underexplored. LeRoux et al . now show how the DNA-targeting ADP-ribosylation activity of DarTG impairs phage replication but is overcome by dedicated viral inhibitors and evolved tolerance.